A “sétima arte” que fecha a janela da alma: representações da ideologia do crescimento organizacional nos filmes norte-americanos vencedores do Oscar - Mendonça, Fernando Augusto (2014)
Analyzing the dominant literature on management is attributed as the correct understanding that the business organizational growth is the best or only alternative to business success and survival in competitive markets (Alison, John, and Shameem, 2003; Davidsson, 1989 ; Frederic Delmar, Davidsson & Gartner, 2003; Greve, 2008; Harvard University, 1998; Penrose, 1959; Speller & Rabelo, 2005; Starbucks 1971, 2005). For alternatives to this model issues can quote Ansoff, 1965; Barney, 1996; Mintzberg, 1994; Porter, 1980 and others. Seifert and Viseu (2015) argue that organizational growth has become one of the main ideologies of modern management. Several studies have indicated that the cultural industry has historically been used as a means for the dissemination of ideology to the masses (Costa Barros and Marting, 2012; Adorno, 2006). In this study, we investigate how the business world has been represented in Hollywood films. More specifically, to understand how representations of the world of business in American films awarded the Oscar has historically been articulated in terms of business growth ideology. The fact of finding fewer and fewer alternatives and critical to the growth ideology, and therefore dialogue on new alternatives to our system, can be related to the ideological content of the films. Methodologically analyzed the 86 films awarded as "Best Film" since the award's inception in 1929. Thirty-nine of them deal directly or indirectly on the business world that were classified as "questioning" or "pro-growth". The latter is subdivided into two subcategories. Then were related dates and periods in which the films were released with major historical events of the time. This allowed understand how the ideology of growth has been represented in the film industry in general; and generated a better understanding of the ideological discourse portrayed in different historical periods. The results suggest that while 11 films awarded as "Best Film" question the ideology of growth in the business world, 28 are pro-growth. The main topics covered by films that question the ideology of growth are: i) conditions in the work environment; ii) the need to decrease; iii) ethical behavior; iv) individualism; v) review for the American dream; and vi) business and family interests. The main topics covered in the films classified as pro-growth were: i) the benefits of growth; ii) the assets of the American dream (development, freedom and consumption); iii) the need to revenue; and iv) the virtues of self-made man. The results also show that there is a strong association between business representations in films and historical events in different periods. For example, it was found that most of the films that question the ideology of organizational growth were launched between 1938 and 1948, whereas after 1950 they naturalized the need for growth or defended openly. This study contributes to a critical understanding of the ideology of organizational growth, and for a better understanding of how the cultural industry has been used as a means of legitimizing the managerial ideology. It is a call to question the idea that organizational growth is the only alternative for business activities.